Experimental IR meets multilinguality, multimodality, and interaction : 9th International Conference of the CLEF Association, CLEF 2018, Avignon, France, September 10-14, 2018, Proceedings /: 9th International Conference of the CLEF Association, CLEF 2018, Avignon, France, September 10-14, 2018, Proceedings. ([2018]) - Unknown
No abstract available